Portfolio performance across genders and generations : the role of financial innovation - Davydov, Denis; Florestedt, Otto; Peltomäki, Jarkko; Schön, Marcus (Elsevier, 2017)
Using a unique dataset on the trading transaction records of private investors from Sweden, we explore the role of gender and age in the use of Exchange Traded Products (ETPs), considered to be innovative investment products, with respect to implications for portfolio performance. We show evidence that investors perform better when trading and investing in mutual funds, but younger investors may be relatively more skillful users of ETPs. We also find that older men and women trade more actively, although they also show a better investment performance, and we emphasize that age and gender are very different demographic determinants of investor behavior and performance.
Keywords: financial innovation; exchange traded product; age; gender; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|